Synthesis and functionalisation of magnetic nanoparticles for hyperthermia applications. (7th October 2013) - Grüttner, Cordula; Müller, Knut; Teller, Joachim; Westphal, Fritz
Abstract: A summary of recent developments in the synthesis, stabilisation and coating of magnetic iron oxide nanoparticles for hyperthermia applications is presented. Methods for synthesis in aqueous, organic and microemulsion systems are reviewed together with the resulting heating rates of the nanoparticles. Different stabilisation mechanisms for iron oxide nanoparticles from aqueous and organic media are discussed as intermediates for further coating and functionalisation. Coating with silica and/or polysaccharides is mainly used for design of nanoparticles especially for targeted hyperthermia application. These coatings permit versatile functionalisation as a basis for conjugating biomolecules, e.g. antibodies or peptides. Various strategies to conjugate biomolecules on the particle surface are discussed, with emphasis on methods that preserve biofunctionality after immobilisation. The efficiency of established methods such as carbodiimide coupling and oriented conjugation strategies is compared with new developments such as the bioorthogonal approaches that are based on the cycloaddition of strain-promoted alkynes with azides or nitrones. For targeted hyperthermia applications the study of the formation of a protein corona around nanoparticles with site-specific biomolecules on the surface is essential to achieve improved circulation times in the blood and reduced non-specific uptake by non-targeted organs for a high specific accumulation in the target tissue.